Exploring the variables influencing the immune response of traditional and innovative glycoconjugate vaccines - Micoli, Francesca; Stefanetti, Giuseppe; MacLennan, Calman A. (Frontiers in Molecular Biosciences, 2023)
Vaccines are cost-effective tools for reducing morbidity and mortality caused by infectious diseases. The rapid evolution of pneumococcal conjugate vaccines, introduction of tetravalent meningococcal conjugate vaccines, mass vaccination campaigns in Africa with a meningococcal A conjugate vaccine and the recent licensure of glycoconjugates against S. Typhi underlie the constant importance of research into glycoconjugate vaccines. Over the years, more innovative ways to produce carbohydrate-based vaccines have been developed, including bioconjugation, Outer Membrane Vesicles (OMV) and Multiple antigen-presenting system (MAPS). Several variables in the design of these vaccines can impinge on the immune responses the vaccines elicit. We review immunogenicity studies that compare conjugate vaccines differing in design variables, such as saccharide chain length and conjugation chemistry, as well as carrier protein and saccharide to protein ratio. We assess how a better understanding of the effects of these different parameters is key to designing improved glycoconjugate vaccines.